2014
DOI: 10.1002/2013jd020633
|View full text |Cite
|
Sign up to set email alerts
|

Near‐cloud aerosol properties from the 1 km resolution MODIS ocean product

Abstract: This study examines aerosol properties in the vicinity of clouds by analyzing high-resolution atmospheric correction parameters provided in the MODIS (Moderate Resolution Imaging Spectroradiometer) ocean color product. The study analyzes data from a 2 week long period of September in 10 years, covering a large area in the northeast Atlantic Ocean. The results indicate that on the one hand, the Quality Assessment (QA) flags of the ocean color product successfully eliminate cloud-related uncertainties in ocean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…The analysis used data collected over the northeast Atlantic Ocean during ten consecutive Septembers. Similar to the analysis of CALIPSO data [20], the results of MODIS data analysis showed that sampling of different cloud fractions near clouds and far from clouds can explain a significant but not dominant part (15%-30%) of the near-cloud AOT changes reported earlier [29]. For particle size, however, analyzing the Atlantic Ocean southwest of the United Kingdom yielded some opposite behaviors than the area near the Azores [20]: While sampling different cloud fractions near and far from clouds strengthened the near-cloud particle size changes in the composite statistics of the Azores, this effect weakened the near-cloud particle size changes in our composite statistics.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The analysis used data collected over the northeast Atlantic Ocean during ten consecutive Septembers. Similar to the analysis of CALIPSO data [20], the results of MODIS data analysis showed that sampling of different cloud fractions near clouds and far from clouds can explain a significant but not dominant part (15%-30%) of the near-cloud AOT changes reported earlier [29]. For particle size, however, analyzing the Atlantic Ocean southwest of the United Kingdom yielded some opposite behaviors than the area near the Azores [20]: While sampling different cloud fractions near and far from clouds strengthened the near-cloud particle size changes in the composite statistics of the Azores, this effect weakened the near-cloud particle size changes in our composite statistics.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, the resampling made near-cloud particle size changes even stronger in our dataset-which implies that resampling would strengthen the particle size changes discussed in [29]. We also found that the exact method of resampling makes very little difference for optical thickness, and only a modest difference for particle size (characterized through the Angstrom exponent).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…There is also the limitation that cloud and aerosol properties cannot be obtained simultaneously over the same location. Recent studies have revealed that the aerosol optical depth (AOD) retrieved in the presence of nearby clouds can be significantly enhanced (Jeong and Li 2010;Várnai and Marshak 2014), which can lead to spurious correlations between aerosols and cloud properties (Costantino and Bréon 2013). These limitations can be ameliorated, or overcome, by using ground and in situ observations, which have already been used to investigate the influence of aerosols on cloud microphysical properties (Feingold et al 2001McComiskey et al 2009;Twohy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Under such scenarios, the situation is far more complicated due to changes in the physical and optical properties of aerosol in a humidified atmosphere near to the cloud zone [ Altaratz et al ., ], which has important consequences on the Earth's radiation balance [ Feingold and Morley , ]. Satellite and in situ observations have detected enhanced aerosol optical depth (AOD) near clouds, confirming radiative forcing anomalies when compared with cloud‐free zones [ Charlson et al ., ; Su et al ., ; Wen et al ., ; Várnai et al ., ; Várnai and Marshak , ]. On the other hand, new particles formed around growing convective clouds can also enhance the background aerosol number concentration and serve as cloud condensation nuclei that influence the radiative properties [ Hegg et al ., ; Perry and Hobbs , ; Clarke et al ., ; Heintzenberg and Charlson , ].…”
Section: Introductionmentioning
confidence: 99%